2002
DOI: 10.1046/j.1468-1331.2002.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

No difference in efficacy of two different doses of intravenous immunoglobulins in MS: clinical and MRI assessment

Abstract: We performed a double-blind, placebo-controlled study to evaluate the efficacy of low and high dose of intravenous immunoglobulins (IVIG) in relapsing/remitting (RR) multiple sclerosis (MS). Patients (n = 49) with clinical definite RR MS were randomly allocated to three groups and treated with 0.2 g/kg (n = 17) or 0.4 g/kg (n = 15) once a month of IVIG and placebo (n = 17) for 12 months. Clinical data were assessed monthly and magnetic resonance imaging (MRI) was performed every 3 months during the study perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 43 publications
2
54
0
1
Order By: Relevance
“…Four studies in RRMS were positive, three with clinical endpoints [5][6][7] and one with MRI endpoints [8]. One study in clinically isolated syndrome (CIS) patients showed significant postponement of conversion to definite MS [9].…”
mentioning
confidence: 99%
“…Four studies in RRMS were positive, three with clinical endpoints [5][6][7] and one with MRI endpoints [8]. One study in clinically isolated syndrome (CIS) patients showed significant postponement of conversion to definite MS [9].…”
mentioning
confidence: 99%
“…IVIg has been shown effective in the treatment of some immune mediated diseases like idiopathic thrombocytopenic purpura, Kawasaki disease, Guillain-Barre syndrome, dermatomyositis and many others [11] and carries the potential of modifying and/or reversing a number of the immunologic abnormalities found in MS. IVIg treatment has a beneficial effect on MS using both clinical and MRI endpoints [12]. MS is an immune-mediated disorder affecting the CNS that is thought to result from destruction of myelin that is produced by oligodendrocytes by autoreactive T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Long-range ivIg therapy (long-term interval therapy) of this type of MS was shown to improve symptoms and reduce the number of relapses [2,3,26,31,37,70,77,112,113,115,116]. In patients with high relapse rates and clinical disease progression ivIg therapy is indicated especially during pregnancy and lactation, in childhood and also if IFN-β, Copaxone and nataluzimab are contraindicated.…”
Section: Relapsing Multiple Sclerosis (Ms)mentioning
confidence: 99%